Secondary flow behavior of electrolytic viscous fluids with Bird-Carreau model in curved microchannels - Yoon, Kyu; Jung, Hyun Wook; Chun, Myung-Suk (SPRINGER, 2017)
A curved channel is indispensable for the lab-on-chips system because it provides a convenient scheme for increasing the channel length per unit chip area in the direction of net flow. A secondary Dean flow in curved rectangular microchannels is examined by applying a finite volume scheme with a semi-implicit method for pressure-linked equations revised (SIMPLER) algorithm for the steady flow of non-Newtonian fluids with dilute concentrations in electrolyte solution. The proposed framework is based on a theoretical model coupled with the Cauchy momentum equation of Bird-Carreau fluid, electrostatic interaction, and net charge conservation. The shear thinning effect on the secondary flow at the turn is analyzed with respect to the parameters of interest including zero-shear viscosity and power-law index. The simulation results for the realistic microchannel indicate that the streamwise axial velocity tends to shift toward the inner wall and this is caused by a stronger spanwise pressure gradient, resulting from a sufficiently low Dean number. In the case of the non-Newtonian fluid, the axial velocity becomes a blunt profile by spreading to each side of the wall, and its flow skewness directed asymmetrically to the inner wall is higher than that in the case of the Newtonian fluid. The attaining trend of higher flow skewness is changed by the competing effect of shear thinning and is well matched with the behavior of the secondary flow.
Keywords: NON-NEWTONIAN FLUIDS; RECTANGULAR MICROCHANNELS; SURFACE; PIPES; MICROFLUIDICS; CAPILLARY; TRANSPORT; CHIP